Platymerella—a cool-water virgianid brachiopod fauna in southern Laurentia during the earliest Silurian. (January 2023) - Jin, Jisuo; Santamaria, Jose; Mikulic, Donald; Chowns, Timothy
Abstract: Platymerella from the lower Red Mountain Formation in Georgia and Tennessee, the Bowling Green Dolomite of west-central Illinois, and the Elwood Dolomite of northeastern Illinois represents a paleosubtropical, cool-water occurrence of virgianid brachiopods in Laurentia during the early Silurian (middle–late Rhuddanian). These occurrences were located in the southern Appalachian foreland basin and the distal end of the Sebree Trough, likely subjected to frequent cool-water current and upwelling from Gondwana. Compared with broadly coeval species of Virgiana from lower paleotropical to equatorial latitudes, Platymerella has significantly smaller, dorsoventrally flattened shells, with subequal ventral and dorsal umbones and beaks that extend only slightly above the hinge line. Relative to its shell size, however, Platymerella has more prominent thickening of the shell wall, median septum, spondylium, and hinge plates than Virgiana, resembling more closely the extravagant shell thickening of Tcherskidium and Proconchidium from the Late Ordovician (late Katian) equatorial regions. The thickening of hinge plates resulted in the formation of a pseudocruralium, which separates Platymerella from Virgiana . In latest Ordovician–earliest Silurian virgianids, there was a general morphological gradient toward a smaller shell, reduction in the ventral-valve convexity, and reduction in the size and height of the ventral umbo from paleoequatorial to southern subtropical regions, with Platymerella representing the most southerly forms.